Selection and study of structure and properties thermal gas coating of piston ring dual-purpose machines - Гнатюк, Анастасія Анатоліївна (Харківський національний автомобільно-дорожній університет, 2022)
The object of research is steel-molybdenum coatings to increase the wear resistance of piston rings of dual-purpose machines with the formation of special structures and properties of surface layers of parts to increase durability. The purpose of the work is to solve the scientific and technological problem of increasing the durability of piston rings of dual-purpose machines based on the use of steel-molybdenum coating for the formation of special structures and properties of surface layers. The research method is optical and electron microscopy, X-ray structural analysis, microhardness measurement, laboratory and operational tests of wear resistance of piston rings. In the thesis, the peculiarities of gas-thermal coating formation during simultaneous electric arc spraying of molybdenum and 11X18M steel on piston rings made of cast iron are established. It is shown that a layered structure is formed, consisting mainly of steel and molybdenum particles. The reasons for the wide range of properties of steel and molybdenum particles are clarified. It has been proven that the operational properties of the steel-molybdenum coating are determined by its anti-friction properties, porosity, which ensures self-lubrication of the friction surface, good adhesion with the substrate, which increases 3-4 times compared to traditional methods.
Keywords: structure; surface treatment; piston ring; steel-molybdenum coating; hardness; wear resistance